2020
DOI: 10.18632/aging.103287
|View full text |Cite
|
Sign up to set email alerts
|

Leisure activities and disability in activities of daily living among the oldest-old Chinese population: evidence from the Chinese Longitudinal Healthy Longevity Study

Abstract: Introduction: To investigate the independent and joint effects of leisure activities on disability in activities of daily living (ADL) among the oldest-old Chinese population (aged ≥ 80 years). Results: A total of 3696 participants with ADL disability were identified during the median follow-up period of 3.1 years. Compared to the participants who "never" watched TV or listened to the radio and who "never" kept domestic animals or pets, those who engaged in these activities "almost every day" had a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 49 publications
2
10
0
Order By: Relevance
“…In general, baseline ADL, age, leisure activity, Disability level is constantly progressing as age increases [4,11]. Some researchers have shown that leisure activity is strongly associated with the risk of disability [46,47]. Cognitive impairment has a significant impact on disability and they are mutually reinforcing over time [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…In general, baseline ADL, age, leisure activity, Disability level is constantly progressing as age increases [4,11]. Some researchers have shown that leisure activity is strongly associated with the risk of disability [46,47]. Cognitive impairment has a significant impact on disability and they are mutually reinforcing over time [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Tai Chi was reported to improve physical performance and hemodynamic outcomes in a 48-week randomized clinical trial among adults aged ≥70 years and may reduce the risk of future frailty [40]. Prolonged TV watching was found to be a risk factor for frailty and functional limitations in European older adults [41] but might prove beneficial to adults aged ≥80 years by reducing the risk of cognitive impairment [16, 42]. Keeping pets [43, 44] and playing cards or Mahjong were also protective factors against frailty [45].…”
Section: Discussionmentioning
confidence: 99%
“…Exercise is a recognized frailty prevention factor [1,[12][13][14] but high prevalence of daily living disability limits the access of adults aged ≥80 years to regular exercise [15,16]. Leisure activities also have the potential to impact frailty in this population, and greater understanding of this association would be an advantage.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from physical performances, our updated model yielded the following independent risk factors: gender, age, smoking, self-report health condition, BMI, depressive symptoms, and cognitive function. Older age, smoking, overweight or underweight, poor self-reported health conditions, or poor mental health are commonly associated with ADL disability [30,31]. Most modifiable risk factors may reverse the decline of ADL disability and easy-to-measure variables that discriminate well in predicting functional decline in community-dwelling older adults.…”
Section: Discussionmentioning
confidence: 99%
“…The following variables were also considered as predictors: age, gender, marital status, education, social activity, drinking, smoking, night sleep, comorbidities, body mass index (BMI), self-assessment of health conditions, depressive symptoms, and cognitive function [30,31]. Age was classified into the following four groups: 60-64, 65-69, 70-74, and older than 75 years old [32].…”
Section: Other Predictorsmentioning
confidence: 99%